Lectures historiques et apprentissage de l’histoire chez les filles et les garçons, 1700-1815. Une analyse sérielle de leurs souvenirs - Pierre Caspard (Genre & Histoire)
Before the French school system took responsibility for it, in the course of the XIXth century, the teaching of history was largely informal, both for boys and girls. In XVIIIth century France, the autonomy of families, including of children themselves, was prominent. That must not be a hindrance to the search for some regularities in the learning practices of these children: they bear testimony in historical memoirs, memories and autobiographies. We have systematically analysed 156 of them, 122 written by men, 34 by women born between 1700 and 1815. They say a lot about the kinds of historical books which were respectively read by girls and boys, the ages at which they read them, whether under the supervision of adults or not, the means of appropriating their contents, orally or in writing, the contribution made to the imaginary world of boys and girls, as well as to their personal, religious and political culture. The article brings out the great closeness of the historical readings and learnings of girls and boys, while pointing out some specificities which it tries to explain.